Star polynomials of some families of graphs with small cyclomatic numbers - Farrell E.J.; De Matas C.M. (Utilitas Mathematica, 2000)
Explicit formulae are derived (in terms of chains) for the star polynomial of generalized stars (long stars), generalized theta-graphs and the basic graphs with cyclomatic number 2.